Crossing of the epithelial barriers by Bacillus anthracis: the Known and the Unknown - Goossens, Pierre L.; Tournier, Jean-Nicolas (Frontiers in Microbiology, 2015)
Anthrax, caused by Bacillus anthracis, a Gram-positive spore-forming bacterium, is initiated by the entry of spores into the host body. There are three types of human infection: cutaneous, inhalational, and gastrointestinal. For each form, B. anthracis spores need to cross the cutaneous, respiratory or digestive epithelial barriers, respectively, as a first obligate step to establish infection. Anthrax is a toxi-infection: an association of toxemia and rapidly spreading infection progressing to septicemia. The pathogenicity of Bacillus anthracis mainly depends on two toxins and a capsule. The capsule protects bacilli from the immune system, thus promoting systemic dissemination. The toxins alter host cell signalling, thereby paralysing the immune response of the host and perturbing the endocrine and endothelial systems. In this review, we will mainly focus on the events and mechanisms leading to crossing of the respiratory epithelial barrier, as the majority of studies have addressed inhalational infection. We will discuss the critical gaps of knowledge that need to be addressed to gain a comprehensive view of the initial steps of inhalational anthrax. We will then discuss the few data available on B. anthracis crossing the cutaneous and digestive epithelia.